2021
DOI: 10.6007/ijarbss/v11-i4/9678
|View full text |Cite
|
Sign up to set email alerts
|

Success Factors of Rural Entrepreneurs in Malaysia: The Proposed Model

Abstract: Entrepreneurial activities, especially among rural entrepreneurs has become one of the contributing factors to economic development. Various studies and literature had discussed the factors influencing toward entrepreneurship success which will affect the growth and sustainability of business performance. As the Malaysian economy is affected by covid-19, people can no longer rely on job opportunities. Engaging in entrepreneurial activities is the best way to help improve the economy whether for individuals, fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Also, previous study by Cragg and King (1998) argue that financial performance of small businesses is strongly influenced by the markets where they operate as well as entrepreneur's objectives, characteristics and management practices (Islam et al, 2011;Ridzwan et al, 2021). Othman and Rosli (2011) in their literature survey found that marketing resources and capital structure mix of enterprises as well as previous experience, skill and educational level of the owners are factors influencing small business performance.…”
Section: Smes Performancementioning
confidence: 98%
“…Also, previous study by Cragg and King (1998) argue that financial performance of small businesses is strongly influenced by the markets where they operate as well as entrepreneur's objectives, characteristics and management practices (Islam et al, 2011;Ridzwan et al, 2021). Othman and Rosli (2011) in their literature survey found that marketing resources and capital structure mix of enterprises as well as previous experience, skill and educational level of the owners are factors influencing small business performance.…”
Section: Smes Performancementioning
confidence: 98%